Efecto de porcentajes de aceite de girasol y variedades de maní para obtención de una crema en la Microempresa MANATOS - Zambrano Cedeño, Angela Cecibel (2023)
The purpose of the work was to determine the physicochemical, microbiological and organoleptic effects produced by the percentages of sunflower oil and peanut varieties in obtaining a cream in the Manatos microenterprise. A completely randomized design was used in a bifactorial arrangement A * B + 1 (Schullo peanut butter), factor A with two levels (Caramelo and Charapotó) and factor B sunflower oil with three levels at 2.5%, 5% and 7.5. %, resulting in 7 treatments and 21 experimental units of 250 g. The physicochemical parameters (fat content, sodium chloride, humidity and free acidity), microbiological (molds and yeasts and E. coli) were studied, and in the sensory analysis the degree of acceptability was calculated by 75 untrained judges. The physicochemical results showed that the treatments in the fat content presented highly significant statistical differences, on the other hand the results in sodium chloride, humidity, acidity in all the treatments comply with what is prescribed in the NTE INEN 276 standard. The microbiological results of all the treatments presented absences in molds and yeasts. In the organoleptic attributes evaluated, the tasters considered the treatments T1 (caramel peanuts and 2.5% sunflower oil) and T4 (Charapotó peanuts and 2.5% sunflower oil) to be more acceptable. With the results obtained, it can be established that the peanut variety does not affect the acceptability for obtaining a cream.